Analysis of Ectopic Pregnancy at Paropakar Maternity and Women’s Hospital - Shakya, Beemba (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To analyze the patients with ectopic pregnancy. Methods: The medical records of 88 ectopic pregnancies at Paropakar Maternity and Women’s Hospital were reviewed from January to July 2020. Data pertaining patient characteristics, age, gravida, risk factors, clinical presentation, diagnostic modality, site of ectopic pregnancy, management and morbidity associated with it were retrieved and was analyzed using SPSS version 16.0. Results: Among 88 ectopic pregnancies, 28% occurred in 30-34 years,65% were multipara, presented abdominal pain (72%), vaginal bleeding (60%) and amenorrhoea (57%); 72% had ampullary ectopic, 60% had ruptured ectopic, 99% underwent surgical management and 41% required blood transfusion. There was no any mortality. Conclusions: Abdominal pain, vaginal bleeding and amenorrhoea were the common presentation. Only 60% had ruptured ectopic pregnancy. Almost all had surgical management.